Pola Asuh Orang Tua Dengan Tingkat Kecemasan Remaja Putri Dalam Menghadapi Menarche - dr wibisono; Alfin Kurniati (Jurnal Kesehatan, 2020)
ABSTRACT Young women aged 10-16 years will experience menarche (first menstruation). This will cause physical tension, anxiety in the bad things that will happen when menarche. The purpose of this study was to determine the relationship of parenting parents with the level of anxiety of adolescent girls in facing menarche in class V and VI students at SDN Bojong 1 Tangerang District in 2019. The research method used in this study was descriptive correlation with cross sectional approach. The population in this study amounted to 62 respondents with the technique used for data collection is total sampling by distributing questionnaire sheets that have been valid and reliable. Univariate and bivariate data analysis using Chi-Square and Correlation. The results of the study are based on the Chi-Square test and produce a p value = (0.001 <0.05) then it is stated that there is a relationship between parenting patterns and the level of anxiety of adolescent girls in dealing with menarche. Conclusions and suggestions based on the results of the study there is a significant relationship between parenting parents with the level of anxiety of young women in dealing with menarche in class V and VI students at SDN Bojong 1 Tangerang District. It is recommended that young women be more open to problems with parents in order to get the right information and knowledge.